Foliar application of salicylic acid intensifies antioxidant system and photosynthetic efficiency in tomato plants - Aires, Eduardo Santana [UNESP]; Ferraz, Andrew Kim Lopes [UNESP]; Carvalho, Beatriz Lívero [UNESP]; Teixeira, Fabrício Palla [UNESP]; Rodrigues, João Domingos [UNESP]; Ono, Elizabeth Orika [UNESP] (Instituto Agronômico de Campinas, 2022)
Tomatoes are the most important and grown vegetable crop in the world. The salicylic acid (SA) application could improve crop yields due the positive physiological effects of this plant growth regulator. Thus, this study aimed to evaluate the possible effects of SA application on leaf regarding the intensification of antioxidant enzymes activities, chlorophyll a fluorescence, gas exchange, and tomato production against environmental stress. This experiment was conducted by the use of Colossal tomato hybrid in a protected environment between July and December 2019. Therefore, a randomized block design with five SA doses was used, as follows: 0; 0.5; 1; 1.5, and 2 mM. Then, applications were performed weekly from 15 to 60 days after transplantation (DAT). At the 45th and the 60th DAT, the enzymes activities were analysed, such as superoxide dismutase (SOD), catalase activity (CAT) and peroxidase (POD), lipid peroxidation, proline content, chlorophyll a fluorescence, gas exchange, and plant height. At the end of the experiment, fruit weight, total and commercial production were also evaluated. Results indicated that foliar application of SA reduced the environmental stress in plants through the intensification of antioxidant system that reduced lipid peroxidation and qNP and increased the efficiency of photosystem II and ETR. Furthermore, gas exchange was also influenced by the action of SA in gs, favouring A and A/Ci. The SA dose between 0.5 and 0.8 mM positively enabled the total and commercial production of tomatoes. Therefore, foliar application of SA reduced oxidative damage, and increased photosynthetic efficiency and fruit production.
Keywords: photosynthesis; production; plant growth regulator; Solanum lycopersicum